Molecular Detection and Coat Protein Gene Mutation Analysis of Potato Leafroll Virus and Potato Virus Yin Bangladesh (Plant Tissue Culture and Biotechnology, 2026)
Potato (Solanum tuberosum) production in Bangladesh faces significant threats from viral diseases, particularly Potato Leafroll Virus (PLRV) and Potato Virus Y (PVY). This study was designed to investigate the prevalence and molecular characteristics of these viruses across three major potato-growing districts: Rangpur, Jamalpur, and Gazipur. Twenty-four samples collected during the 2023 harvest were analyzed using DAS-ELISA and RT-PCR techniques. Coat protein (CP) gene-specific primers facilitated amplification and sequencing of viral isolates. Results revealed high infection frequencies, including notable mixed infections. Sequence analysis identified six PLRV and five PVY isolates harboring distinct missense mutations. Phylogenetic analysis indicated close genetic relationships with isolates from  India, China, and South Africa,  suggesting possible transboundary virus introduction. Identified mutations may influence viral movement, protein function, and transmission efficiency. These findings provide valuable baseline data on the genetic diversity of potato-infecting viruses in Bangladesh, offering critical implications for seed potato certification, disease management, and agricultural biosecurity programs.Plant Tissue Cult. & Biotech. 36(1): 149-164, 2026 (June)